Numerical investigation for acoustic performance improvement of a forklift exhaust muffler with the influence of flow and temperature fields. (January 2023) - Zhang, Enlai; Chen, Yi; Tian, Shuwen; Chen, Xianyi
In order to improve the acoustic performance of an internal combustion forklift exhaust muffler, this paper considered the influence of air flow and temperature, based on the flow field analysis theory, the exhaust muffler's fluid domain model at the highest engine speed was established, that is, the complex flow and temperature fields were numerically simulated with a computational fluid dynamics (CFD) model, and the acoustic calculation was carried out by the finite element mothod (FEM), obtaining the velocity and temperature cloud maps and transmission loss curve. In addition, according to the simulation results, the improvement strategy towards intake pipe structural parameters was proposed. Numerical simulations indicate that for the improved exhaust muffler, flow eddy regions are obviously decreased, temperature gradient distribution is uniform, the transmission loss in most frequency bands and the overall sound attenuation effect are improved, which will lay a technical foundation for future physical application and multi-field coupling research.